A proposed framework for solving conflicts of mining projects - Álvarez, César (2015)
The purpose of this paper, is to propose a framework for solving conflicts of mining projects, based on the inclusion of: a) the alignments to the project management framework of the Project Management Institute, b) the implementation of an Integrated Sustainable Development Program, c) a public surrender of accounts, and d) the continuous audit processes by internal institutions and by external, independent and international institutions. This proposed framework was contextualized to the Tía María mining project in Peru; also, a generic solution framework is presented. Finally, some recommendations for future researches were proposed.